Análisis jurídico del derecho a la educación a personas con discapacidad intelectual y la aplicación de políticas públicas - Paredes Jaramillo, Erika Cristina (2024)
The present research work includes a legal study of the right to education for people with intellectual disabilities and the application of public policies, which has been a problem since these public policies are not sufficient to guarantee the rights of these people. carrying out a detailed analysis of existing policies for the inclusive education of people with intellectual disabilities, identifying possible obstacles and proposing improvements. In addition, we seek to understand the legal and institutional framework that supports these policies, in order to guarantee the full exercise of the right to education for this group of people. Where, it will also focus on proposing specific recommendations to promote the effective inclusion of people with intellectual disabilities in the general educational system. Despite legal advances, people with disabilities face discrimination and exclusion in various aspects of society, including mobility, employment and access to public services. The lack of these effective public policies and adequate legal mechanisms to make their rights effective aggravates this situation. In addition, the lack of training in regulations and physical inaccessibility are additional barriers that prevent the full integration of people with disabilities. On the other hand, inclusive education is a key policy to ensure that people with disabilities can access quality education, which not only implies access to education but also the provision of additional supports, teaching materials and adapted teaching strategies. to the needs of each student. It should be noted that this research covers a broad analysis of legal information, from a descriptive, evaluative, explanatory and propositional perspective, under a legal guideline in the legal framework of the right to education. In addition, various materials and methods were used that allowed the development of the research. Interviews and surveys were also carried out with legal professionals, the results of which highlight the 4 importance of generating a critical vision regarding the right to inclusive education of people with intellectual disabilities and the application of effective public policies in order to guarantee a correct comprehensive development in the educational field.